2003
DOI: 10.1002/14651858.cd003665
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation for prevention of morbidity and mortality in preterm infants

Abstract: Vitamin E supplementation in preterm infants reduced the risk of intracranial hemorrhage but increased the risk of sepsis. In very low birth weight infants it increased the risk of sepsis, and reduced the risk of severe retinopathy and blindness among those examined. Evidence does not support the routine use of vitamin E supplementation by intravenous route at high doses, or aiming at serum tocopherol levels greater than 3.5 mg/dl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
195
1
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(210 citation statements)
references
References 123 publications
3
195
1
11
Order By: Relevance
“…High-dose parenteral vitamin E supplementation or serum levels 480 mM are not recommended (Brion et al, 2003). In the present study, four (13%) of VLBW infants in contrast to none of the NBW infants had a-tocopherol concentrations 480 mM.…”
Section: Fat-soluble Vitaminscontrasting
confidence: 55%
See 2 more Smart Citations
“…High-dose parenteral vitamin E supplementation or serum levels 480 mM are not recommended (Brion et al, 2003). In the present study, four (13%) of VLBW infants in contrast to none of the NBW infants had a-tocopherol concentrations 480 mM.…”
Section: Fat-soluble Vitaminscontrasting
confidence: 55%
“…C Henriksen et al of vitamin E have been proposed as an antioxidant to limit retinopathy, cerebral hemorrhage, hemolytic anemia and chronic lung disease with sepsis as a potential toxic side effect (Brion et al, 2003). High-dose parenteral vitamin E supplementation or serum levels 480 mM are not recommended (Brion et al, 2003).…”
Section: Fat-soluble Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,24 Studies show that in low income situations there is a change in food choices, characterized by the acquisition of cheaper items and with high energy density. 7,22,23 The first items that are out of the diet are usually the healthier food, which the population cannot reach the recommended quantities, such as grains of high quality protein, vegetables and greenery, extra virgin olive oil and fresh fruit, 6,22,25 some important sources of vitamin E.…”
Section: Tablementioning
confidence: 99%
“…When present, the deficiency in neonates is associated to hemolytic anemia, bilirubin, thrombocytosis, intracranial hemorrhage and retrolental fibroplasia. 6,7 There are few studies that investigate the associated factors with maternal vitamin E deficiency (DVE). Gurgel et al 8 found a high prevalence of the deficiency in women attended for the delivery in public maternities when compared to those attended at a private health network.…”
Section: Introductionmentioning
confidence: 99%